The state of the art of PSP and the Software Industry - Pando Soto, Brian Cesar (2018)
The measurement of efforts made by people engaged in software development has been hardly done in software engineering. The SEI proposes a set of practices for time management and personal productivity improvement of programmers or software engineers for software development and maintenance tasks, by monitoring and comparing the planned performance versus actual performance, which Watts Humphrey in the 90s named the Personal Software Process (PSP). The research that were reviewed show that, at a global level, the skills of engineers who join the software industry do not satisfy software industry expectations, and how PSP contributes to skills enhancement.